COVID-19 Significantly Affects Maternal Health: A Rapid-Response Investigation from Pakistan - Ali, Inayat; Sadique, Salma; Ali, Shahbaz (Frontiers in Global Women's Health, 2020)
The coronavirus disease 2019 (COVID-19) is still unfolding. Its several implications are visible, yet we have to observe and witness in future. Dealing with these impacts, this rapid-response article aims to situate the COVID-19 pandemic within Pakistan’s overall sociocultural and politico-economic context; next to investigate the impacts of COVID-19 particularly the psychological ones on pregnant women in Pakistan via five case studies. One case history of Haleema (pseudonym) revealed how the pandemic exerted a substantial amount of mental pressure due to “arranging someone to accompany her to the hospital, finding a blood donor for her, and insecurity of convenience to hospital.” In this article, we show that Pakistan’s geographical division into wealthier urban and more impoverished rural areas may facilitate disease transmission in these more deprived areas, that cultural norms and mores such as shaking hands, cheek-kissing, and hugging that spread the virus are being overturned and that pregnant women are particularly vulnerable to psychological effects of the pandemic.